Electrochemical Analysis of Glycoprotein Samples Prepared on a Pneumatically‐controlled Microfluidic Device. Issue 10 (12th June 2019) - Novotny, Jakub; Ostatna, Veronika; Foret, Frantisek
Abstract: In this work, we designed and manufactured a microfluidic device for isolation and purification of glycoprotein samples. The conceived sample preparation device was fabricated in polycarbonate by micro‐milling. The flow control and the fluid dosage into the micro‐channels was solved by equipping the device with integrated pneumatic valves. The biochemical functionality was provided by beaded support modified by molecules with affinity to glycoproteins which was stacked inside the micro‐channel reminiscent of packed affinity columns used in glycoprotein lectin assays. Unlabeled glycoproteins, namely fetuin, asialofetuin, and prostate‐specific antigen, were voltammetrically analyzed using catalytic peak H at silver amalgam electrode. Abstract :